The historical development of orientalism movement in Malaysia: An analysisal-takfir according to ahl al-sunnah wa al-jama'ah and its relation to national unity - Engku Ahmad Zaki, Engku Alwi; Normah, Yusof (Medwell Journals, 2019)
This study attempts to analyse orientalist movement in Malaysia, especially, their thoughts which are supposed to influence the Malaysian society. This movement was related to the colonization of Malaysia by the Portuguese, Dutch and English. The they collected all information from books and manuscripts to be adapted as academic research with orientalist will.